Design And Build Electric Trolly To Accelerate The Distribution Of Goods In The Warehouse - Ali Imron; Izza Anshory (Universitas Muhammadiyah Sidoarjo, 2022)
Using manual trolly because it takes a long time and is quite draining. The purpose of this study is to make a breakthrough tool that can help in the process of distributing goods in the warehouse so as to make time more efficient and not drain so much energy that the employee expends. In the manufacture of this electric trolly there are 2 methods, namely the first in making this trolly design can be climbed by the trolly driver The second method of this trolly moves with a 24V dc motor and there is a load cell sensor so that the trolly user can know the weight of the goods transported by this trolly then there is an infrared sensor to read the rotation of the trolly wheel and the reading results of the loadcell and infrared sensor are managed by the arduino microcontroller. From the results of the research, this tool runs according to its function, which is to be able to assist the work of employees in distributing goods in the warehouse so that it can make work time more efficient.